Cross-country typologies and development strategies to end hunger in Africa - Zhang, Xiaobo; Johnson, Michael E.; Resnick, Danielle; Robinson, Sherman (International Food Policy Research Institute, 2004)
The key motivation behind this study is to explore the many patterns of interactions between economic and non-economic factors in sub-Saharan Africa (hereafter referred to as Africa) in order to map out a typology of different types of country situations and thus, corresponding future options to develop strategies to end hunger and poverty in the region. The study builds on the earlier work of Irma Adelman and Cynthia Morris who argued that economic development is a dynamic, multi-faceted, nonlinear, and malleable process, a process explained by the many complex interactions between social, economic, political and institutional changes. As in Adelman and Morris, we use factor analysis to reduce a large number of variables into a manageable set of key factors. Next, using the newly developed classification and regression tree technique (CART), we link the outcome variables, such as per capital GDP and the prevalence of child malnutrition, with this smaller set of factors. This overcomes the limitations of Adelman and Morris. work that mixed the outcome and explanatory variables in their analysis. The analysis helps identify the most important factors for each outcome indicator, which provides guidance for defining the development of a typology and exploring future strategy options associated with each country type.